2011
DOI: 10.1103/physrevb.83.075202
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of grain boundary sinks and interstitial diffusion in neutron-irradiated SiC

Abstract: The widths of interstitial loop denuded zone (DZ) along grain boundaries were examined for 3C-SiC irradiated at 1010-1380˚C by transmission electron microscopy in an effort to obtain the activation energy of interstitial migration. DZ widths as small as 17 nm were observed below 1130˚C, indicating that a substantial population of "TEM invisible" voids of diameter <0.7 significantly contribute to interstitial annihilation. Using the obtained loop DZ width and the matrix sink strength including the invisible voi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 20 publications
(24 reference statements)
1
22
1
Order By: Relevance
“…We found only one experimental work on electron RIA of b-SiC [21], which predicts T cr = 340 K. This value is larger than the amorphization temperature found in our no-barrier model (T cr = 263 K) and lower than those found in the recombination (T cr = 450 K) and trapping (T cr = 475 K) models. One possible source of the discrepancy in T cr is the presence of high density of stacking faults in experimental samples, which defects are common for pre-irradiated single crystal b-SiC [21,17]. It is possible that these stacking faults both destabilize the bulk phase vs. amorphization and serve as sinks for irradiation-induced point defects and therefore could alter T cr from what it would be for an ideal undefected bulk sample.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We found only one experimental work on electron RIA of b-SiC [21], which predicts T cr = 340 K. This value is larger than the amorphization temperature found in our no-barrier model (T cr = 263 K) and lower than those found in the recombination (T cr = 450 K) and trapping (T cr = 475 K) models. One possible source of the discrepancy in T cr is the presence of high density of stacking faults in experimental samples, which defects are common for pre-irradiated single crystal b-SiC [21,17]. It is possible that these stacking faults both destabilize the bulk phase vs. amorphization and serve as sinks for irradiation-induced point defects and therefore could alter T cr from what it would be for an ideal undefected bulk sample.…”
Section: Discussionmentioning
confidence: 93%
“…These energies are necessary to understand fundamental processes underlying damage evolution on diffusive time scales. Long term microstructural evolution of irradiated SiC has been studied primarily using experimental methods [14][15][16][17]. A comprehensive review of studies in this area can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…2 A lower value of about 0.8 eV 43,50 has been reported for the migration barrier of Si I . However, based on the dependence of interstitial loop denuded zone (DZ) width on temperature along grain boundaries in 3C-SiC, 46 the activation energy for migration of Si interstitials has been determined to be about 1.5eV. Therefore, a close value of 1.48eV reported in Ref.…”
Section: Okmc Simulation For Long-term Defect Evolutionmentioning
confidence: 99%
“…Most of these parameters come from a recent ab-initio calculation by D. Shraders et al, 43 while a few parameters are adopted from other works 44,46 for the following reasons: 1…”
Section: Okmc Simulation For Long-term Defect Evolutionmentioning
confidence: 99%
“…Defect denuded zones (DDZs) in the vicinity of defect sinks are typically observed after radiation at high temperature. For instance, DDZs along grain boundaries (GBs) were reported in SiC after neutron irradiation at 1010-1380°C [7]. Under light or heavy ion irradiation at 650°C, DDZs formed near the surface or adjacent to GBs in MgAl 2 O 4 and Al 2 O 3 [5].…”
Section: Introductionmentioning
confidence: 98%